Planting methods, subsurface drip fertigation and bioinoculants on growth and productivity of vetiver [Vetiveria zizanioides (L.) Nash] - A S Anilkumar, G J Shimi, (Journal of Spices and Aromatic Crops, 2014)
A field experiment was conducted to study the effect of three planting methods, (planting in coconut husk mulched trenches, planting in coconut husk lined trenches and planting on the ridges), two levels of fertigation (subsurface drip fertigation and without fertigation) and two levels of bioinoculants (combined application of bioinoculants and without bioinoculant) on growth and productivity of vetiver. The study revealed that planting vetiver slips in coconut husk lined trenches could considerably increase vegetative growth, root yield, net returns and B: C ratio. Subsurface drip fertigation and combined application of bioinoculants with Azospirillum, Fluorescent pseudomonads and AM fungi showed positive effect on growth characters and root yield. However, subsurface drip fertigation was not effective in increasing net income.